The Effect of Transcatheter Aortic Valve Implantation on Pulmonary Hypertension. Issue 7 (17th October 2014) - Durmaz, Tahir; Ayhan, Hüseyin; Keleş, Telat; Aslan, Abdullah Nabi; Kasapkara, Hacı Ahmet; Sarı, Cenk; Bilen, Emine; Akar Bayram, Nihal; Akçay, Murat; Bozkurt, Engin
<x xml:space="preserve">Abstract</x> Background and Aim Pulmonary hypertension (PH) is common in patients with severe aortic stenosis (AS). The prognostic effect of PH in high‐risk patients undergoing transcatheter aortic valve implantation (TAVI) remains unknown. The aim of this study was to examine the feasibility of TAVI in patients with PH and to determine the effect of TAVI on PH. Methods and Results TAVI was performed in 70 patients (mean age, 77.6 years; 51 females and 19 males) between July 2011 and December 2012, in our hospital. The patients were divided into three groups based on their systolic pulmonary artery pressure (sPAP) values. Group 1 comprised patients with sPAP values <40 mmHg; group 2 included patients with sPAP values ranging from 40 to 59 mmHg; and group 3 included patients with sPAP values >60 mmHg. Seventy percent of the patients were in groups 2 and 3. After TAVI, the sPAP values of the patients in groups 2 and 3 were significantly decreased (47.4 ± 4.6 and 36.6 ± 6.3, P < 0.001 and 64.5 ± 4.7 and 43.2 ± 9.2, P < 0.001, respectively). However, this reduction was sustained for 6 months in group 2 (P = 0.006), whereas the reduction lost its statistical significance (P = 0.07) after 1 month in group 3 (64.5 ± 4.7 and 40.8 ± 8.0, P = 0.001). Significant differences between the sPAP values in all three groups before the procedure were sustained after TAVI (P ≤ 0.001) and after the 1st month (P = 0.02); however, no statistically significant difference was observed after the 6th month (P = 0.06). Conclusion In this study, we demonstrated that TAVI could be reliably and successfully performed in PH patients with severe AS and that TAVI results in a permanent and significant reduction in sPAP.